Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fpubh.2022.792015
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors, Formation Mechanism, and Pre-control Methods of Coal Miners′ Unsafe Behavior: A Systematic Literature Review

Abstract: Coal mine accidents are mainly caused by the unsafe behavior of workers. Studying workers' unsafe behaviors can help in regulating such behaviors and reducing the incidence of accidents. However, there is a dearth of systematic literature review in this area, which has hindered mine managers from fully understanding the unsafe behavior of workers. This study aims to address this research gap based on the literature retrieved from the Web of Science. First, a descriptive statistical analysis is conducted on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 113 publications
1
8
0
Order By: Relevance
“…In addition, some scholars used only literature reviews to summarize relevant articles and then summarized the infuencing factors. In combination with scholars' historical research results and the actual situation of coal mine security management, Yang et al [66] classifed the factors afecting unsafe behavior by coal miners in detail in terms of individual factors, organizational management factors, and environmental factors. Chen et al [67] classifed the factors infuencing (un)safe building behaviors into four levels: individual, group, organization, and society.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, some scholars used only literature reviews to summarize relevant articles and then summarized the infuencing factors. In combination with scholars' historical research results and the actual situation of coal mine security management, Yang et al [66] classifed the factors afecting unsafe behavior by coal miners in detail in terms of individual factors, organizational management factors, and environmental factors. Chen et al [67] classifed the factors infuencing (un)safe building behaviors into four levels: individual, group, organization, and society.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The unsafe behavior of miners refers to the behavior miners exhibit that fails to strictly comply with safety rules and regulations in the production process, which may have a negative impact on organizational and personal safety [32]. For the staff of a transport roadway, these behaviors can be generally divided into two categories: "operator error" and "venturing into dangerous places" [33].…”
Section: Definition Of Unsafe Behavior Of Miners In a Transport Roadwaymentioning
confidence: 99%
“…It is worth noting that the front-line miners' behavior can directly affect coal mine safety production [2]. Previous studies have confirmed that miners' behavior is governed by both external factors (work environment and organizational management) and internal factors (personal traits and psychological state) [3]. Particularly, managers with primary power play a key role in shaping and encouraging miners' behavior.…”
Section: Introductionmentioning
confidence: 98%
“…Personal traits are significant internal factors affecting the behavioral choice of miners [3]. Work values are the personal traits expressed by employees at work, reflecting their inner needs and value orientation, and serving as the value criteria for judging work behaviors [5].…”
Section: Introductionmentioning
confidence: 99%